2019
DOI: 10.1016/j.ijscr.2019.06.062
|View full text |Cite
|
Sign up to set email alerts
|

C-arm cone-beam computed tomography-guided minimally invasive open excision of an osteoid osteoma undetectable on fluoroscopy: A case report

Abstract: Highlights A robotic C-arm cone-beam computed tomography (CBCT) system provides a clear intraoperative visualization of the osteoid osteoma. C-arm CBCT allowed precise access to the tumor, accurate tumor resection, and minimal sacrifice of the normal bone in osteoid osteoma surgery. Repurpose use of the dilator, retractor, and wider trephine tips achieved more conservative results with a smaller skin incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The clinical outcomes of this study are comparable to that of a previous study. [ 12 ] Higuchi et al reported a case of successful resection under CBCT guidance for invisible osteoid osteoma by regular biplane fluoroscopy. [ 12 ] However, to the best of our knowledge, there is a lack of literature on CBCT-guided curettage for osteoid osteoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical outcomes of this study are comparable to that of a previous study. [ 12 ] Higuchi et al reported a case of successful resection under CBCT guidance for invisible osteoid osteoma by regular biplane fluoroscopy. [ 12 ] However, to the best of our knowledge, there is a lack of literature on CBCT-guided curettage for osteoid osteoma.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT use reduces the risk of intraoperative infections, which may occur during transportation from the radiation facility. [ 12 ] Meanwhile, in conventional CT-guided excision, postoperative fracture, infection, hematoma, and nerve injury were reported as postoperative complications. [ 21 ] In a study of CT-guided resection of osteoid osteoma in the femur, 2 femoral fractures (4.8%) were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation